The World of Vaccines: Phases of Clinical Trials and Current Status of COVID-19 Vaccines - Pabbathi, Navya; Pasupulati, Haritha; Gaddam, Soni; SV Padi, Satyanarayana (Asian Journal of Pharmaceutical Research and Development, 2023)
The world of vaccines has transformed vaccination by saving millions of lives which otherwise would have killed many people and a hurdle for sustainable development world-wide. Indeed, the coronavirus disease 2019 (COVID-19) pandemic is a public health emergency and an important milestone that revealed how vaccines are really turning point for live changing across the world. Owing to extensive human efforts, vaccines for COVID-19 are discovered and developed and approved globally in less than a year, which is the first time in the history of the world of vaccines. Furthermore, one of the strategic goals of WHO’s ‘The Immunization Agenda 2030’ (IA2030) is the clinical development and approval of 500 new vaccines by 2030. Discovery of immunogens that elicit immune responses is a key step or process by which vaccine candidates have been optimized for further preclinical and clinical trials. Clinical evaluation is carried out in Phases (1-3) and is a sequential approach of establishing safety and efficacy in humans. Regulatory requirements for vaccine approval and licensure to bulk manufacturing are another hurdle. Further, post-marketing safety studies and post-marketing surveillance (Phase 4) are essential to collect the real-world data on safety and effectiveness of the approved vaccines. This review work provides a brief outline on timeline of development of traditional and COVID-19 vaccines and summarizes all the six stages of the vaccine development. Furthermore, current status of COVID-19 vaccines is discussed in view of future approvals.